ANALISIS KEPUASAN PENGGUNA SISTEM INFORMASI E-CAMPUS DI IAIN BUKITTINGGI MENGGUNAKAN METODE EUCS - Arif Saputra; Denny Kurniadi (Universitas Negeri Padang, 2019)
This study aims to find out and analyze how the level of user satisfaction with an information system is being used, and to find out what factors influence the level of user satisfaction of the Information System. The object of this research is the E-Campus information system at the Islamic Institution of Bukittinggi state. Research is based on the importance of evaluation for the development of a system. The method used in this study is End User Computing Satisfaction (EUCS). The EUCS method consists of five independent variables, namely content, accuracy, shape, ease of use and timeliness and one dependent variable is satisfaction. Population data is N = 99 with the analysis results obtained by the correlation coefficient number of 73.3%. That is, there is a statistically positive relationship between content, accuracy, form, ease of use, timeliness, and satisfaction. if each variable has a higher correlation, it will increase the user satisfaction of the E-Campus Information System with the meaning of the relationship in the same direction.Keywords: End User Computing Satisfaction (EUCS), satisfaction, information system, E-Campus.